Using authentic teaching materials to improve reading comprehension of Islamic Economic Law students - Zahrina Zahrina (English Education Journal, 2017)
This research was conducted to revise teaching materials for reading comprehension for the study of Islamic Economic Law at Al-Hilal College, Sigli. During teaching English, the writer (as the lecturer) presented reading materials taken from the textbook and they were less connected to the need of students of Islamic Economic Law Department. Thus, she decided to use up to date authentic materials taken from websites and online newspapers. The subjects for this research were 37 students in their first semester in the Department of Islamic Economic Law. The instruments used were observation check-lists, a test, a questionnaire, and field notes. The data was analysed qualitatively and quantitatively. Furthermore, there were three cycles in this research. The result of observation checklists showed that the writer reached the improvements from first to last cycle, respectively marked by 76%, 86% and 88%. Moreover, observation check-lists also exposed the students’ improvements - they increased significantly from 74% to 87% and 89% after each cycle. Additionally, the students’ average test results increased positively from 38% to 75%. The questionnaire result proved that the students’ perceptions on significance of using authentic materials were 91%, while 97% agreed with the useful of the texts presented during teaching learning. Lastly, through the document- i.e. field notes; the writer noticed that the students’ vocabulary related to Islamic Economic Law increased.